Aneuploidy enables cross-tolerance to unrelated antifungal drugs in Candida parapsilosis - Sun, Liu-liu; Li, Hao; Yan, Tian-hua; Cao, Yong-bing; Jiang, Yuan-ying; Yang, Feng (Frontiers in Microbiology, 2023)
Candida parapsilosis is an emerging major human fungal pathogen. Echinocandins are first-line antifungal drugs for the treatment of invasive Candida infections. In clinical isolates, tolerance to echinocandins in Candida species is mostly due to point mutations of FKS genes which encode the target protein of echinocandins. However, here we found chromosome 5 trisomy was the major mechanism of adaptation to echinocandin drug caspofungin, and FKS mutations were rare events. Chromosome 5 trisomy conferred tolerance to echinocandin drugs caspofungin and micafungin, as well as cross tolerance to 5-flucytosine, another class of antifungal drugs. The inherent instability of aneuploidy caused unstable drug tolerance. Tolerance to echinocandins might be due to increased copy number and expression of CHS7, which encodes chitin synthase. Although copy number of chitinase genes CHT3 and CHT4 was also increased to trisomic level, the expression was buffered to disomic level. Tolerance to 5-flucytosine might be due to decreased expression of FUR1. Therefore, the pleiotropic effect of aneuploidy on antifungal tolerance was due to the simultaneous regulation of genes on the aneuploid chromosome and genes on euploid chromosomes. In summary, aneuploidy provides a rapid and reversible mechanism of drug tolerance and cross tolerance in C. parapsilosis.